2020
DOI: 10.31557/apjcp.2020.21.8.2415
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2B, AP-1 and JAZF1 Expression in Tissues of Papillary Thyroid Carcinoma Patients; Clinical, Pathological and Prognostic Values

Abstract: Objective: Transcription factor activating protein 2 B (TFAP2 B) is a transcription factor that regulates many steps of embryogenesis, cell growth, apoptosis and recently oncogenesis and cancer progression. AP-1 is a transcription factor that is a downstream molecule of the MAPK signaling pathway. Juxtaposed with zinc finger gene 1 (JAZF1) is a recently detected transforming growth factor which has a role in carcinogenesis. Hence the present study aimed to assess those markers expression in tissues from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Notably AP-1 is a transcription factor complex composed of c-Fos and c-Jun dimers, and is a key regulator of tumor cell invasion [47]. AP-1 promotes migration and invasion in a variety of different tumor cell types, such as triple-negative breast, colorectal and thyroid cancer [48][49][50][51][52][53]. Although AP-1 is involved in multiple pathways associated with cancer [52][53][54], the detailed molecular mechanisms are yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably AP-1 is a transcription factor complex composed of c-Fos and c-Jun dimers, and is a key regulator of tumor cell invasion [47]. AP-1 promotes migration and invasion in a variety of different tumor cell types, such as triple-negative breast, colorectal and thyroid cancer [48][49][50][51][52][53]. Although AP-1 is involved in multiple pathways associated with cancer [52][53][54], the detailed molecular mechanisms are yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…AP-1 promotes migration and invasion in a variety of different tumor cell types, such as triple-negative breast, colorectal and thyroid cancer [48][49][50][51][52][53]. Although AP-1 is involved in multiple pathways associated with cancer [52][53][54], the detailed molecular mechanisms are yet to be fully elucidated. Collectively, results of the present study demonstrated that NGEF is a downstream gene of AP-1 associated with BRAF V600E -mutant thyroid cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Disease Markers JUN, a key component of dimeric transcription factor activator protein-1 (AP-1), plays a role in the transcriptional response to extracellular signaling [37]. A previous study showed that AP-1 expression in papillary thyroid carcinoma cancer tissue is positively correlated with a high incidence of disease progression, a high tumor recurrence rate, and unfavorable disease-free survival [38]. In our experimental group, JUN expression was downregulated in PTC cells after Disease Markers quercetin treatment.…”
Section: Discussionmentioning
confidence: 99%